Respuesta :
Answer:
[tex]\mathsf {z = \frac{41}{24}}[/tex]
Step-by-step explanation:
[tex]\textsf {Given :}[/tex]
[tex]\mathsf {\frac {2x + y - 3z}{y + 3x} = \frac{x}{2y} }[/tex]
[tex]\textsf {Substituting the values given (x = 1, y = 4) :}[/tex]
[tex]\mathsf {\frac {2(1) + 4 - 3z}{4 + 3(1)} = \frac{1}{2(4)} }[/tex]
[tex]\mathsf {\frac {6 - 3z}{7} = \frac{1}{8} }[/tex]
[tex]\textsf {Cross multiply the values :}[/tex]
[tex]\mathsf {8(6 - 3z) = 7}[/tex]
[tex]\mathsf {48 - 24z = 7}[/tex]
[tex]\mathsf {24z = 41}[/tex]
[tex]\mathsf z = {\frac{41}{24}}[/tex]
Answer:
[tex]z=\dfrac{41}{24}[/tex]
Step-by-step explanation:
Given equation:
[tex]\dfrac{2x + y - 3z}{y + 3x} = \dfrac{x}{2y}[/tex]
Given:
- [tex]x=1[/tex]
- [tex]y=4[/tex]
Substitute the given values of x and y into the given equation:
[tex]\implies \dfrac{2(1) + 4 - 3z}{4 + 3(1)} = \dfrac{1}{2(4)}[/tex]
[tex]\implies \dfrac{6-3z}{7}=\dfrac{1}{8}[/tex]
Cross multiply:
[tex]\implies 8(6-3z)=7[/tex]
Expand the brackets:
[tex]\implies 48-24z=7[/tex]
Subtract 48 from both sides:
[tex]\implies -24z=-41[/tex]
Divide both sides by -24:
[tex]\implies z=\dfrac{41}{24}[/tex]